PENGARUH RISIKO BISNIS DAN PAJAK TERHADAP STRUKTUR MODAL STUDI EMPIRIS PADA PERUSAHAAN SEKTOR REAL ESTATE, PROPERTY AND BUILDING CONSTRUCTION YANG TERDAFTAR DI BEI - Aprilia Fitriani; M Mardi; Susi Indriani (Faculty of Economics, State University of Jakarta., 2014)
This study aimed to examine the effect of business and tax risks partially or simultaneously to the company's capital structure esatate estate sector, property and building construction are listed in Indonesia Stock Exchange with a sample of 37 companies. This study uses ex post facto with quantitative data. Observations were made in the financial statements. Collecting data using observation and collection of documents. While the method of analysis using descriptive statistics, the classical assumption test and multiple regression analysis. Descriptive analysis showed that: a) the average value of each variable can be used as a representation of all the data, b) the transmission frequency of the range interval classes are in either category because no frequency is zero. While the classical assumption test results showed that: a) the normal distribution of data, b) does not occur multicollinearity, c) does not occur heteroscedasticity, d) no autocorrelation. Regression test showed results that a) partially influential business risk significantly to the capital structure, b) partially tax does not affect the capital structure, c) simultaneously and taxes affect business risk significantly. Keywords: Capital Structure, Business Risk